(untitled) - Nguyễn, Mai Thy (Cần Thơ, 2020)
This study aimed to investigate the impact of story-telling on EFL young learners’ reading comprehension and their perceptions towards the use of story-telling in learning and teaching reading English at a foreign language center in the Mekong Delta of Vietnam. The study was an experimental study using both quantitative and qualitative methods. Data was gathered from reading comprehension tests, questionnaire and interviews. The participants were at the age of 10-12 years old. They were assigned into two groups. The experimental group consisted of 9 students who were taught reading with story-telling and the control group included 10 students who were taught reading aloud without story-telling. The quantitative method of pretest and posttest were used to evaluate the impact of story-telling on learners’ reading comprehension performance. Questionnaire was used to obtain students’ perceptions towards the use of story-telling in reading in English lessons. The qualitative method of interviews was conducted to gain in-depth information about students’ perceptions about the use of story-telling for learning reading. The findings of study indicated that students of two groups obtained high scores after the study. Both story-telling and teacher’s reading aloud had a great impact on developing students’ reading comprehension. Even though students learned with reading aloud obtained higher results in terms of reading comprehension performance as being compared with students in the experimental group. The learners who instructed with story-telling had made a big progress in their reading performance after the study. Most importantly, the use of story-telling can increase students’ motivation and make students more concentrated in learning. Limitations and recommendations for effective implementation of story-telling in an EFL context were also provided in this study.
Keywords: Anh ngữ,English language; Dạy và học,Study and teaching